SOSIALISASI PERAN UMKM DAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 GUNA MENDORONG MASYARAKAT SADAR PAJAK - Amir Hidayatulloh; Fina Dwi Fatma (Jurnal Pengabdian UntukMu NegeRI, 2019)
Tax is the main source of state revenue. In 2018, the source of state revenues of 85,40% came from the tax sector. So large, state revenue from tax sector, encourage the government in increase taxpayer compliance. However, the realization of revenue from the tax sector in January-November has not yet reached the target. In 2018, the government issued a government regulation that was imposed on taxpayers who have certain gross income. So, with the issuance of government regulation it is hoped that the public can play an active role in economic activities. This service was carried out in Banjaran Hamlet, Sukoreno, Sentolo, Kulon Progo, Special Regional of Yogyakarta. This service is shown to MSME players. This service technique uses lecture, sharing and discussion methods. The result of this service activity is to increase the knowledge of MSME actors regarding the benefits of NPWP, the reason MSME actors must pay taxes, and tax benefits. In addition, this service also found the reason for MSME not to make NPWP, as well as the reason for MSME actors not to apply Government Regulation Number 23 of 2018. In addition, MSMEs did not understand the importance of separating entrepreneurial capital from their own capital. Keywords: Tax. MSME, Regulation Number 23 of 2018, NPWP